2020
DOI: 10.1155/2020/8475910
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effectiveness between Cobalt Chromium Rods versus Titanium Rods for Treatment of Patients with Spinal Deformity: A Systematic Review and Meta-Analysis

Abstract: Background. Biomechanical properties of rods determine their ability to correct spinal deformity and prevention of postoperative sagittal and coronal changes. The selection of a proper rod material is crucial due to their specific mechanical properties that influence the surgical outcome. The purpose of this study is to compare the effectiveness of cobalt chromium rods versus titanium rods for the treatment of spinal deformity by a systematic review and meta-analysis. Methods. PubMed, EMBASE, and the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In our study, among patients who had a 3CO, we found significantly higher usage of supplemental rods in Group II, and this may have contributed to the lower incidence of rod breakage. Other work indicated that the use of titanium rods was associated with a lower incidence of PJK compared with cobalt-chromium because of rod stiffness 26,27 . The usage of titanium rods was higher in Group II, while the use of cobalt-chromium remained constant, suggesting that the rod material may have also contributed to the diminished likelihood of PJF that we observed in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, among patients who had a 3CO, we found significantly higher usage of supplemental rods in Group II, and this may have contributed to the lower incidence of rod breakage. Other work indicated that the use of titanium rods was associated with a lower incidence of PJK compared with cobalt-chromium because of rod stiffness 26,27 . The usage of titanium rods was higher in Group II, while the use of cobalt-chromium remained constant, suggesting that the rod material may have also contributed to the diminished likelihood of PJF that we observed in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the financial limitations imposed by our National Health Insurance system, titanium rod remains the sole option for posterior spinal instrumentation in our healthcare setting. Previous literature suggests that cobalt-chromium rods are generally considered better than titanium rods for effectively reducing the rate of rod fractures, correcting spinal deformities, and ensuring postoperative stability ( 27 , 28 ). Limited to using titanium rods, we need to increase pedicle screw density to effectively and safely perform the reduction by derotation technique with the rods.…”
Section: Discussionmentioning
confidence: 99%
“…Barton, Solla, and Farah used titanium rods, Kleck and Prost and Pesenti did not specify, Prost and Farah used titanium rods for 47 patients with cobalt chromium rods for the other 39 and Sadrameli used all cobalt chromium rods. The cobalt chromium rods are stiffer and believed to obtain higher rates of deformity correction but associated with an increased risk of proximal junctional kyphosis [ 45 ]. Construct properties such as screw type/number/placement, hooks, and cross connectors were only reported in one included manuscript despite being known to affect complication rates [ 46 ].…”
Section: Discussionmentioning
confidence: 99%